Medical cannabinoids for treatment of neuropsychiatric symptoms in dementia: a systematic review - Stella, Florindo [UNESP]; Valiengo, Leandro C Lane; Paula, Vanessa J R de; Lima, Carlos Augusto de Mendonça; Forlenza, Orestes V. (EDITORA SCIENTIFIC, 2021)
INTRODUCTION: Neuropsychiatric symptoms are an integral component of the natural history of dementia, occurring from prodromal to advanced stages of the disease process and causing increased burden and morbidity. Clinical presentations are pleomorphic and clinical management often requires combinations of pharmacological and non-pharmacological interventions. However, limited efficacy and a non-negligible incidence of adverse psychotropic drug events emphasize the need for novel therapeutic options. OBJECTIVES: To review the evidence supporting use of medical cannabinoids for treatment of neuropsychiatric symptoms (NPS) of dementia. METHODS: We conducted a systematic review of the medical literature to examine scientific publications reporting use of medical cannabinoids for treatment of NPS. Medical Subject Headings (MeSH) were used to search for relevant publications and only papers reporting original clinical information were included. A secondary search was performed within selected publications to capture relevant citations that were not retrieved by the systematic review. The papers selected were categorized according to the level of evidence generated by the studies in relation to this clinical application, i.e. (1) controlled clinical trials; (2) open-label or observational studies; and (3) case reports. RESULTS: Fifteen publications with original clinical data were retrieved: five controlled clinical trials, three open-label/observational studies, and seven case reports. Most studies indicated that use of medical cannabinoids engendered favorable outcomes for treatment of NPS related to moderate and advanced stages of dementia, particularly agitation, aggressive behavior, sleep disorder, and sexual disinhibition. CONCLUSION: Medical cannabinoids constitute a promising pharmacological approach to treatment of NPS with preliminary evidence of benefit in at least moderate to severe dementia. Controlled trials with longitudinal designs and larger samples are required to examine the long-term efficacy of these drugs in different types and stages of dementia, in addition to their adverse events and risk of interactions with other drugs. Many pharmacological details are yet to be determined, such as dosing, treatment duration, and concentrations of active compounds (e.g., cannabidiol [CBD]/ Δ9-tetrahydrocannabinol [THC] ratio) in commercial preparations of medical cannabinoids.
Keywords: cannabidiol; Dementia; neuropsychiatric symptoms; treatment; Δ9-tetrahydrocannabinol